EFFECT OF ANTIHYPERTENSIVE DRUGS ON QUALITY OF LIFE IN PATIENTS WITH ARTERIAL HYPERTENSION - G. F. Andreeva; A. D. Deev; V. M. Gorbunov (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To study effect of antihypertensive drugs on quality of life (QoL) of patients with stable arterial hypertension (HT). Material and methods. Results of some studies with similar design involving totally 170 patients with HT, aged 57,2±8,8 y.o., were analyzed. HT duration was 11,2±8,3 years. Patients received antihypertensive monotherapy with diltiazem, amlodipine, enalapril, lisinopril, metoprolol and telmisartan during 1-3 months. 24-hour blood pressure (BP) monitoring, QoL was performed before and after treatment. Results. All antihypertensive drugs significantly reduced systolic and diastolic BP and did not affect QoL. ACE inhibitors similarly improved QoL. Conclusion. Antihypertensive drugs (diltiazem, amlodipine, enalapril, lisinnopril, metoprolol, telmisartan) do not worsen QoL of patients with HT.